Applying Simulation-Based Activities in Interpretation Subject - Yenni Rozimela (International Conference on Languages and Arts, 2012)
This paper presents the merits and drawbacks of simulation- based activities applied in Interpretation subject. At the English Department of UNP, the Interpretation subject is aimed to develop students’ interpretation skills, which in turn enables the graduates to take hold of various job opportunities required these skills. Through interpretation activities, the students improve their language skills, especially listening and speaking. In addition, they are trained to develop some other-related communication skills such as interviewing people and presenting a paper in a seminar.  In other words, the students develop their communication skills. To resemble the real events of interpretation, simulation-based activities are used in the class. They are talk-show, seminar, and drama.  The students are given the roles in accordance with the activities. Here, the teaching and learning activities and the results obtained through the writer’s observation and field-notes will be presented. The problems the students face and the difficulties in carrying out the activities also need to be noted as they can be useful input for future improvement both for Interpretation and other related subjects.   Keywords: Interpretation, Simulation, Seminar, Drama, Talk-Show